Case Report: CBD Cigarettes for Harm Reduction and Adjunctive Therapy in a Patient With Schizophrenia and Substance Use Disorder - Meyer, Maximilian; Walter, Marc; Borgwardt, Stefan; Scheidegger, Alexandra; Lang, Elisabeth; Köck, Patrick (Frontiers in Psychiatry, 2021)
The treatment of patients with schizophrenia and substance use disorder poses a challenge for clinicians. Continued use of cannabis and cocaine can exacerbate psychotic symptoms and worsen the course of disease. To date, no pharmacotherapy is available for patients with cannabis use disorder (CUD). Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) are the main active constituents in Cannabis sativa, with the latter being linked to an increased risk of psychosis. We describe a clinical case of a male patient diagnosed with schizophrenia, combined personality disorder, CUD and cocaine use disorder. Over the course of eight years, he was hospitalized 30 times due to psychotic relapses and continued substance use. Consequently, CBD cigarettes with a low THC content (<1%) were used as adjunctive therapy. Additionally, we established off-label treatment with methylphenidate to support abstinence. The patient reported to feel significantly less need to consume illegal cannabis with a high THC content. He stopped to use cocaine, for the time being, and has not been hospitalized since. This case report demonstrates the potential of smoked CBD as a substitute for severe and chronic CUD.